The Role of puns in Enhancing Japanese Language Learning for English Major Students - Andi Rachmawati Syarif; Sam Hermansyah; Nursidah (Institut Agama Islam Negeri Palopo, 2024)
This study examines the role of puns in Japanese language learning among Indonesian students majoring in English who are taking Japanese elective courses. Puns have various functions in teaching and learning Japanese as a Foreign Language (JFL). This study investigates the role of puns in Japanese language learning. This study used a mixed methods approach, collecting data through questionnaires from 54 students. The findings show that using puns in JFL classes has a positive effect on learning Japanese. The Beneficial Aspects of Using Japanese Puns in the Classroom, (1). Improving Vocabulary Comprehension; (2) Developing Speaking skills; (3) Introducing Aspects of Japanese Culture; (4). Improving Hiragana and Katakana Reading Skills. This research makes a novelty contribution by examining puns in the specific context of English majors studying Japanese. In addition, this study proposes a teaching model that utilizes puns as a tool to connect aspects of humor, creativity, and cultural understanding in the learning process.